Bioefficiency of Insecticide Products on German Cockroach (Blattella germanica) - Sathantaipop, Sunaina; Suphapathom, Kasin; Phaeporn, Phankasem (Journal of Health Science of Thailand, 2018)
The objective of this study was to compare the effectiveness of insecticide products in term of bioefficiency. In all, 285 product samples were investigated and the data on types and concentrations of the active ingredients labeled on insecticide products collected from October 2005 to September 2009. It was found that most of the product samples contained pyrethroid insecticides such as cypermethrin (92 products), deltamethrin (46 products) and bifenthrin (30 products). The data also showed that deltamethrin, etofenprox and cypermethrin produced faster knockdown against German cockroaches (KT95), 95 percent of cockroaches were knocked down within 7-15 minutes whereas fenobucarb (within 35-37 minutes) and bifenthrin (within 32-45 minutes) produced slower knockdown against the cockroaches. Chlorpyrifos, fipronil and diazinon had KT95 values over 1 hour of testing however they showed 100 percent mortality at 72 hours after treatment.